2005
DOI: 10.1507/endocrj.52.675
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Neuroblastoma Causing Ectopic ACTH Syndrome

Abstract: Abstract.A 39-year-old woman who presented with typical Cushingoid appearance (moon facies, central obesity, purpura) was admitted to our hospital because of pulmonary infection. She was found to have hypertension, severe hypokalemia, and metabolic alkalosis. Endocrine data revealed elevated plasma levels of ACTH and cortisol with lack of circadian rhythm, non-suppressibility to high-dose dexamethasone, and hyperresponsiveness to CRH stimulation. Although no pituitary mass was detected by MRI of the brain, inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Although there are several possible causes of false-negative findings mainly due to anatomical abnormalities of venous drainage, false-positive cases have been rarely reported [26,27]. In our series, two cases showed positive result of IPS sampling (Case 4) and normal response to CRH stimulation (Case 8), which may be partly explained by tumor venous drainage closest to the cavernous sinus [5] and the possible trough period of cyclic hormonosingle institution in Japan.…”
Section: Managementmentioning
confidence: 55%
See 2 more Smart Citations
“…Although there are several possible causes of false-negative findings mainly due to anatomical abnormalities of venous drainage, false-positive cases have been rarely reported [26,27]. In our series, two cases showed positive result of IPS sampling (Case 4) and normal response to CRH stimulation (Case 8), which may be partly explained by tumor venous drainage closest to the cavernous sinus [5] and the possible trough period of cyclic hormonosingle institution in Japan.…”
Section: Managementmentioning
confidence: 55%
“…Diagnostic imaging test by SRS not available in Japan yet was approved by the Ethics Committee of TMDU Hospital; written informed consent was obtained from each patient. Some cases have been reported elsewhere [5][6][7][8][9][10].…”
Section: Patientsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have reported secretion of adrenocorticotropic hormone (ACTH) from esthesioneuroblastomas (17)(18)(19)(20)(21)(22)(23)(24) . Syndrome of inappropriate antidiuretic hormone (SIADH) has also been reported in patients with esthesioneuroblastoma (9,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) .…”
Section: Discussionmentioning
confidence: 99%
“…Eight cases have previously been described [22][23][24][25][26][27][28]. Ectopic ACTH production, stimulating cortisol secretion and producing Cushing's syndrome, is most commonly a result of small cell lung carcinomas, bronchial carcinoids, and islet cell tumors [29,30].…”
Section: Ectopic Acth Syndromementioning
confidence: 99%